Potential secondary poisoning risks to non‐targets from a sodium nitrite toxic bait for invasive wild pigs. Issue 1 (5th September 2017) - Snow, Nathan P; Foster, Justin A; VanNatta, Eric H; Horak, Katherine E; Humphrys, Simon T; Staples, Linton D; Hewitt, David G; VerCauteren, Kurt C
Abstract : A new toxic bait is under development to curtail invasive wild pigs in the USA and Australia. This bait has low risks of secondary poisoning for non‐target species. Abstract: BACKGROUND: An acute and orally delivered toxic bait containing micro‐encapsulated sodium nitrite (MESN), is under development to provide a novel and humane technology to help curtail damage caused by invasive wild pigs ( Sus scrofa ). We evaluated potential secondary risks for non‐target species by: testing whether four different types of micro‐encapsulation coatings could reduce vomiting by invasive wild pigs, testing the levels of residual sodium nitrite (SN) in tissues of invasive wild pigs, testing the environmental persistence of SN in vomitus, and conducting a risk assessment for scavengers. RESULTS: Micro‐encapsulation coatings did not affect the frequency of vomiting. We identified no risk of secondary poisoning for non‐target scavengers that consume muscle, eyes, and livers of invasive wild pig carcasses because residual SN from the toxic bait was not detected in those tissues. The risk of secondary poisoning from consuming vomitus appeared low because ∼90% of the SN was metabolized or broken down prior to vomiting, and continued to degrade after being exposed to the environment. Secondary poisoning could occur for common scavengers that consume approximately ≥15% of their daily dietary requirements of digestive tract tissues or undigested bait from carcasses of invasive wild pigs in a rapid, single‐feeding event. The likelihood of this occurring in a natural setting is unknown. The digestive tracts of poisoned invasive wild pigs contained an average of ∼4.35 mg/g of residual SN. CONCLUSION: Data from this study suggest no risks of secondary poisoning for non‐target species (including humans) that consume muscle, liver, or eyes of invasive wild pigs poisoned with a MESN toxic bait. More species‐specific testing for scavengers that consume digestive tract tissues and undigested bait is needed to reduce uncertainty about these potential risks. © 2017 Society of Chemical Industry